Feeding ecology of Antarctic toothfish, Dissostichus mawsoni in the subarea 88.3 (Bellingshausen Sea and eastern Amundsen Sea) of the Southern Ocean - Seong, Gi Chang; Chung, Sangdeok; Kim, Do-Gyun; Kang, Da Yeon; Jin, Suyeon; Baeck, Gun Wook (Frontiers in Marine Science, 2023)
Understanding feeding ecology is essential for ecosystem-based management. As dietary data can show differences depending on the spatiotemporal and ontogenetic aspects of the sample, the results should be derived based on various size classes and samples over a wide spatiotemporal range. Morphological analysis of the stomach contents of Dissostichus mawsoni, a piscivore, collected at depths of 603-2,113 m in subarea 88.3 during the Antarctic summer fishing seasons from 2016 to 2020 was used to assess the dietary composition according to the research block, fishing season, depth, and size. Here, we used 1,639 D. mawsoni specimens with a total length range of 44.5-189.0 cm. The dietary composition of D. mawsoni did not show significant differences by fishing season but differed with research block, depth, and size. Macrouridae dominated research blocks 88.3_1 and 88.3_3; Nototheniidae dominated research blocks 88.3_2 and 88.3_6; and Channichthyidae dominated research blocks 88.3_4 and 88.3_5. The proportion of Nototheniidae decreased as depth increased, whereas the consumption of Channichthyidae increased gradually with depth in research blocks 88.3_3 and 88.3_4. The proportion of Channichthyidae decreased as body size increased, whereas the consumption of Macrouridae increased gradually with body size in both blocks 88.3_3 and 88.3_4. During the study period, the dietary composition of D. mawsoni in both blocks 88.3_3 and 88.3_4 did not show significant temporal differences, suggesting that these data could be used as a baseline for identifying future environmental changes in the region. This study provides information on the relationships between various species and benthic fish fauna, which are essential for ecosystem-based management.